From buffalo to human: Klebsiella pneumoniae in high-somatic cell count milk as an overlooked link in the one health chain - Zhifei Wei; Yifei Xiang; Xuelian Mo; Wenjing Li; Erqiang Wang; Changhua Lin; Jiazhou Wei; Yulian Xi; Yuying Liao; Zhengmin Liang; Zhiran Xu; Jiakang He (International Journal of Food Microbiology, 2026)

Seasonal–diurnal nonlinear and interactive associations between built–natural–topographic indicators and land surface temperature in a coastal urban agglomeration - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Sunbowen Zhang; Chuanmao Hua; Chengshu Ke; Yilin Zou (Energy and Buildings, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Comprehensive quality profiling and comparative metabolic characterization of seven dominant fresh-eating Chinese olive (Canarium album Lour.) cultivars in Southern China - Lijuan Fu; Wenjing Liu; Yuying Xu; Xiangxin Lin; Jia Guo; Hao Chen; Jianwei Fu; Sun'an Yan (Food Chemistry, 2026)

Engineering a covalent S-scheme heterojunction in TpBpy/MIL-68(In) to boost interfacial charge transfer for efficient solar-to-hydrogen conversion - Yuying Hu; Huihui Zhang; Jiayi Meng; Yifan Liao; Yuchen Wei; Quanmei Zhou; Mohan Zhang; Yamei Huang; Wei-Lin Dai (Chemical Engineering Journal, 2026)

Co-occurring Spirogyra sp. and enrofloxacin stressors interact to alter macrophyte interactions: evidence from a freshwater mesocosm experiment - Yuqing Tian; Cheng Lin; Xu Zhang; Hui Yang; Hongzhi Mao; Heyin Wang; Jiali Chen; Donghai Zhang; Jiangtao Hu; Xusheng Gong; Junyan Wu; Yuying Li; et al. (Aquatic Sciences, 2026)

Multidimensional analysis of pathogen epidemic patterns, their correlation with milk quality, and drug resistance and virulence traits of dominant pathogenic Escherichia coli in high-somatic-cell buffalo milk: Guangxi, China - Yifei Xiang; Zhifei Wei; Xuelian Mo; Yuying Liao; Chongli Wen; Mengyao Liao; Jiazhou Wei; Changhua Lin; Wenjing Li; Jiaji Chen; Lei Xu; Min Zhu; et al. (Food Microbiology, 2026)

Pt nanoparticles as electron mediators in CdS/AgIn(WO4)2 nanotube heterojunctions for efficient photocatalytic hydrogen evolution - Quanmei Zhou; Jiayi Meng; Yifan Liao; Yuchen Wei; Bite Deng; Yuying Hu; Hongyan Zhao; Yakun Song; Mohan Zhang; Wei-Lin Dai (Chemical Engineering Journal, 2026)

Multi-omics integrated analysis provides insights into developmental mechanisms, metabolic variations and key component biosynthesis in the rare medicinal fungus Gerronema lapidescens - Zhiyuan Jia; Xiaolei Wan; Yuying Liu; Chao Lin; Ming Zhang; Xiaolong He; Haiqiang Wang; Can Du; Minglei Li; Jianzhao Qi (Food Bioscience, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Aged nanoplastics exacerbate CPPD-induced ocular toxicity via the thyroxine pathway in zebrafish - Jin Li; Yi Zheng; Yuying Yin; Wenda Gao; Fan Tang; Xinlin Zhao; Qi Xin; Suiyi Liu; Jiaqi Xiong; Jian Lin; Da Sun; Jiangfei Chen (Aquatic Toxicology, 2026)

Characterization of the ctgf Promoter from Nibea coibor and its Response to TGF-β1 During Collagen Synthesis in Swim Bladder Cells - Ailing Zou; Yuying Yuan; Lingling Zhu; Yu Zhang; Lanfei Xiao; Xiaobo Wen; Fan Lin (Marine Biotechnology, 2026)

Impact of air pollution control strategies on full-phase chlorine species emissions from coal-fired power plants in China during 2013-2022 - Yuying Tang; Yulong Yan; Xionghui Qiu; Zhijian Li; Manli Wang; Zhen Li; Minneng Wen; Wenyi Jin; Yuyang Cheng; Lin Peng (Atmospheric Environment, 2026)

Investigating multi-scale associations and thresholds between eco-environment quality and urban landscape patterns: A case from coastal China - Linsheng Wen; Manuel Esperon-Rodriguez; Yun Peng; Aifang Weng; Yunrui Zhou; Sunbowen Zhang; Baoyin Li; Yuying Lin (Journal of Geographical Sciences, 2026)

Structural and Functional Divergence of the Poecilia picta Sex Chromosomes - Joëlle Lafond; Yuying Lin; Lydia J. M. Fong; Judith E. Mank (Molecular Ecology, 2026)
Sex chromosome evolution has traditionally been viewed as a linear, time‐dependent process. However, numerous comparative studies across diverse taxa have revealed that homomorphy can persist over long evolutionary time scales. Similarly, recent reports of unexpectedly rapid Y chromosome degeneration, particularly in species with evolved X chromosome dosage compensation, suggest alternative evolutionary trajectories that challenge the assumption of gradual decay. However, the mechanisms and consequences of rapid Y chromosome degeneration remain unclear. The Poecilia genus presents a valuable comparative system to investigate these processes, particularly within a clade that shares a recent origin of XY sex chromosomes but exhibits striking variation in sex chromosome morphology. Here, we present a chromosome‐scale assembly of a male P. picta genome using PacBio HiFi reads and Omni‐C data to investigate the extent and consequences of rapid Y‐chromosome degeneration. We find that the Y chromosome is substantially smaller than the X (28.8 Mb vs. 32.6 Mb), contains fewer genes (470 vs. 985) and is heavily enriched in transposable elements, particularly autonomous Helitrons. This degeneration is accompanied by structural divergence and reduced synteny. Concurrently, we document gene traffic from the X chromosome to the autosomes, including male‐benefitting genes such as bbof1 and ssna1 , suggesting a compensatory response to hemizygosity. Together, these results demonstrate rapid structural and functional divergence of the sex chromosomes in P. picta and provide new insights into the dynamics of rapid sex chromosome differentiation.

Lactate-driven histone lactylation enhances GDF15 secretion in skeletal muscle under mtDNA mutation-induced mitochondrial stress - Yan Lin; Busu Li; Jiayin Wang; Weiyue Si; Xingyu Zhuang; Ying Zhao; Wei Jiang; Wei Wang; Dongdong Wang; Fuchen Liu; Ruonan Duan; Yuying Zhao; et al. (Science Bulletin, 2026)

Bioinspired Janus starch film with dual functionality via citral nanoemulsion-mediated interfacial self-assembly for fresh-cut fruits and vegetables preservation - Ying Xie; Yuying Sun; Yawen Li; Ke Ding; Shikai Zhang; Saiqing Xu; Huan Li; Shuhua Lin; Yang Shan; Rongrong Wang; Shenghua Ding (Food Hydrocolloids, 2026)

Fixel-based analysis to detect early fiber-specific white matter alterations in sporadic patients with amyotrophic lateral sclerosis - Mingjie Ma; Qingguo Ren; Xiaohan Sun; Pengfei Lin; Wei Li; Yuying Zhao; Xiangshui Meng; Chuanzhu Yan; Shuangwu Liu (Brain Imaging and Behavior, 2026)

Nano-GlycOTAC eradicates Mycobacterium tuberculosis biofilms and rectifies iron metabolism to augment host antimicrobial immunity - Zhuojun He; Deliang Liu; Yang Zhou; Yao Zhao; Guiqin Dai; Zhiqiang Lin; Siwei Zhang; Xiafei Dai; Yuying Chen; Jinzhi Pan; Huiling Liu; Hong Yu; et al. (Chemical Engineering Journal, 2026)

Ocean Heat Content Sets Another Record in 2025 - Yuying Pan; Lijing Cheng; John Abraham; Kevin E. Trenberth; James Reagan; Juan Du; Zhankun Wang; Andrea Storto; Karina Von Schuckmann; Yujing Zhu; Michael E. Mann; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2026)
Global ocean warming continued unabated in 2025 in response to increased greenhouse gas concentrations and recent reductions in sulfate aerosols, reflecting the long-term accumulation of heat within the climate system, with conditions evolving toward La Niña during the year. In 2025, global upper 2000 m ocean heat content (OHC) increased by ∼23 ± 8 ZJ relative to 2024 according to IAP/CAS estimates. CIGAR-RT, and Copernicus Marine data confirm the continued ocean heat gain. Regionally, about 33% of the global ocean area ranked among its historical (1958–2025) top three warmest conditions, while about 57% fell within the top five, including the tropical and South Atlantic Ocean, Mediterranean Sea, North Indian Ocean, and Southern Oceans, underscoring the broad ocean warming across basins. Multiple datasets consistently indicate ocean warming, as measured by 0–2000 m OHC, increased from 0.14 ± 0.03 W m −2 (10 yr) −1 during 1960–2025 to 0.32 ± 0.14 W m −2 (10 yr) −1 during 2005–2025 (IAP/CAS), the latter being consistent with EEI (Earth’s Energy Imbalance) estimates within uncertainties. In contrast, the global annual mean sea surface temperature (SST) in 2025 was 0.49°C above the 1981–2010 baseline and 0.12 ± 0.03°C lower than in 2024 (IAP/CAS; similar in CMA-SST, FY3 MWRI SST, ERSSTv5 and Copernicus Marine data), consistent with the development of La Niña conditions, but still ranking as the third-warmest year on record.

Dynamics and trade-off/synergy of ecosystem services in China's First Batch national Parks: Evidence from recent decades and future land use and cover changes - Aifang Weng; Baoyin Li; Yuying Lin; Linsheng Wen; Yunrui Zhou; Guo Cai; Sunbowen Zhang; Mir Muhammad Nizamani; Hongxin Wang (Journal of Environmental Management, 2026)

Advances in frosting suppression air source heat pump device: definition and classification - Yao Lin; Wei Wang; Jianfei Luo; Shiquan Wang; Wenzhe Wei; Qing Luo; Yuying Sun; Chuanmin Dai (Energy and Buildings, 2025)

Spatial heterogeneity and nonlinear relationship between landscape ecological risk and drivers: a case of the Qinghai-Tibet Plateau, China - Fazi Zhang; Jingyao Lin; Qiang Wang; Yuying Lin; Niu Dang; Yinan Li (Environment, Development and Sustainability, 2025)

Peptidomics and molecular docking reveal digestion-resistant IgE-binding epitopes in bovine β-lactoglobulin and α-lactalbumin from simulated infant digestion - Fan Yang; Hongwei Zhang; Shaolei Wang; Xue Zhao; Yuying Tang; Jianhua Zeng; Weixue Zhao; Shuo Feng; Changhong Ma; Lanwei Zhang; Kai Lin (Food Chemistry, 2025)

Anion-substitution engineering of indium-based chalcogenide nanocrystals encapsulated into porous carbon microspindles for fast and stable sodium-ion storage - Yafei Li; Yuying Qin; Chunyan Zhu; Xinli Huang; Jing Gao; Chengxiang Wang; Zhiwei Zhang; Yuanchang Shi; Minghao Hua; Xiaohang Lin; Longwei Yin; Rutao Wang (Chemical Engineering Journal, 2025)

Impact of underground wildfire on plant roots in peat soil - Yichao Zhang; Yunzhu Qin; Yuying Chen; Shaorun Lin; Yang Shu; Xinyan Huang; Mei Zhou (CATENA, 2025)

Association of PROP bitter taste sensitivity with anhedonia and emotional eating in the Chinese population - Keying Lin; Yuying Chen; Yue Hua; Jiubo Zhao; Laiquan Zou (Appetite, 2025)

Regulatory Mechanism of CRTC1 on Autophagy and GluA2 Expression in Epilepsy - Xueying Wang; Liqian Zhou; Lin Yang; Shaoping Huang; Yuying Wang; Dan Li (Molecular Neurobiology, 2025)

Unveiling the components, physiological functions and emerging trends of hydroxycinnamic acid amides in goji berry (Lycium) - Siyuan Wei; Yuying Wang; Shiyu Zhou; Shina Luo; Yunuo Lin; Ruixi Wang; Qinyue Jia; Tingting Feng; Guoping Zhao; Xuefeng Yin; Fangwei Yang (Food Research International, 2025)

Underground fires induced by disposed Li-ion battery in peatland and landfill - Yuying Chen; Lei Zhang; Yichao Zhang; Yuxin Zhou; Zifan Zhang; Shaorun Lin; Wei Wei; Xinyan Huang (Process Safety and Environmental Protection, 2025)

Polystyrene nanoplastics chronic exposure cause zebrafish visual neurobehavior toxicity through TGFβ-crystallin axis - Jian Lin; Dongliang Pan; Yangfan Zhu; Baoguo Shen; Zhenkai Sun; Yi Zheng; Yuying Yin; Changjiang Huang; Wencan Wu; Yang Song; Jiangfei Chen (Journal of Hazardous Materials, 2025)

A century of advances in molecular genetics and breeding for sustainable resistance to rice blast disease - Xilai Huang; Wei Yao; Qianru Chen; Jinjun Lin; Jun Huang; Yuying Zou; Chenglong Guo; Bei He; Xiao Yuan; Chengyang Xu; Xionglun Liu; Yinghui Xiao; et al. (Theoretical and Applied Genetics, 2025)

Estimation of construction and demolition waste and assessment of disposal facility location: An integrated Material Flow Analysis and Geographic Information System approach - Yilin Lyu; Nina Xiong; Yuying Liang; Shuqi Lin; Jia Wang (Resources, Conservation and Recycling, 2025)

Characterizing full-phase chlorine species emissions from domestic coal combustion in China: Implications for significant impacts on air pollution and ozone-layer depletion - Wenyi Jin; Yulong Yan; Xionghui Qiu; Lin Peng; Zhen Li; Yuying Tang (Environmental Pollution, 2025)

Conservation tillage increases nutrient accumulation by promoting soil enzyme activity: a meta-analysis - Linsheng Wen; Yun Peng; Yuying Lin; Yunrui Zhou; Guo Cai; Baoyin Li; Baibi Chen (Plant and Soil, 2025)

Experimental study on whole-body comfort perceptions for condensation-free personalized radiant cooling - Yuying Liang; Jianming Yang; Huijun Wu; Xinhua Xu; Zhang Lin; Gongsheng Huang (Building and Environment, 2025)

Photothermal-thermoelectric synergy coupling localized surface plasmon resonance for enhanced flexible photoelectrochemical sensor performance - Mengqi Chen; Hui Tian; Ling Qi; Yuying Zhang; Hongmei Yang; Shenguang Ge; Lina Zhang; Yan Zhang; Lin Li; Kang Cui; Jinghua Yu (Chemical Engineering Journal, 2025)

Excessive accumulation of auxin inhibits protocorm development during germination of Paphiopedilum spicerianum - Yefei Li; Hong Chen; Xinping Kong; Yuying Yin; Ji Li; Kunlin Wu; Songjun Zeng; Lin Fang (Plant Cell Reports, 2025)

Land cover change and its driving factors in Siberia from 1992 to 2020 - Lin Wang; Guimin Liu; Xiaodong Wu; Yunxia Dong; Jun Zhao; Yaoxin Wang; Yuying Li; Meiqi Shao; Xingyuan Cui (Environmental Monitoring and Assessment, 2024)

Evaluation method and enhanced strategy for frosting suppression performance of variable speed air source heat pump based on frosting suppression performance map - Yao Lin; Jianfei Luo; Qing Luo; Xiaoli Li; Wei Wang; Yuying Sun (Energy and Buildings, 2024)

Convergent Neuroimaging and Molecular Signatures in Mild Cognitive Impairment and Alzheimer’s Disease: A Data-Driven Meta-Analysis with N = 3,118 - Xiaopeng Kang; Dawei Wang; Jiaji Lin; Hongxiang Yao; Kun Zhao; Chengyuan Song; Pindong Chen; Yida Qu; Hongwei Yang; Zengqiang Zhang; Bo Zhou; Tong Han; et al. (Neuroscience Bulletin, 2024)
The current study aimed to evaluate the susceptibility to regional brain atrophy and its biological mechanism in Alzheimer’s disease (AD). We conducted data-driven meta-analyses to combine 3,118 structural magnetic resonance images from three datasets to obtain robust atrophy patterns. Then we introduced a set of radiogenomic analyses to investigate the biological basis of the atrophy patterns in AD. Our results showed that the hippocampus and amygdala exhibit the most severe atrophy, followed by the temporal, frontal, and occipital lobes in mild cognitive impairment (MCI) and AD. The extent of atrophy in MCI was less severe than that in AD. A series of biological processes related to the glutamate signaling pathway, cellular stress response, and synapse structure and function were investigated through gene set enrichment analysis. Our study contributes to understanding the manifestations of atrophy and a deeper understanding of the pathophysiological processes that contribute to atrophy, providing new insight for further clinical research on AD.

Regional coordinated development policy as an instrument for alleviating land finance dependency: Evidence from the urban agglomeration development - Danling Chen; Yuying Li; Chaozheng Zhang; Yunlei Zhang; Jiao Hou; Yaoben Lin; Shiman Wu; Yan Lang; Wenbo Hu (Land Use Policy, 2024)

Enhanced sensitivity of extracellular antibiotic resistance genes (ARGs) to environmental concentrations of antibiotic - Huai Lin; Ruiqing Li; Yuying Chen; Yuan Cheng; Qingbin Yuan; Yi Luo (Chemosphere, 2024)

Vegetation greening accelerated hydrological drought in two-thirds of river basins over China - Xin Lan; Yuying Xie; Zhiyong Liu; Ting Yang; Liyan Huang; Xinrong Chen; Xiaohong Chen; Kairong Lin; Linyin Cheng (Journal of Hydrology, 2024)

Exploring the evolution of coupled natural-cultural ecosystem services and their geographically scaled driven modeling in a coastal city of Southeast China - Linsheng Wen; Baoyin Li; Yun Peng; Yunrui Zhou; Aifang Weng; Yidong Jin; Guo Cai; Yuying Lin; Baibi Chen (Journal of Environmental Management, 2024)

Recent advances in swine wastewater treatment technologies for resource recovery: A comprehensive review - Lingling Zhou; Ming Liang; Dongqing Zhang; Xiaojun Niu; Kai Li; Zitao Lin; Xiaojun Luo; Yuying Huang (Science of The Total Environment, 2024)

Inhalation bioaccessibility of imidacloprid in particulate matter: Implications for risk assessment during spraying - Yuying Liu; Fengxiang Lin; Xingyu Yue; Sai Zhang; Han Wang; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Journal of Hazardous Materials, 2024)

Insight into the imbalance of forest cover change at county level in mainland China during 2000–2020: From the perspective of subdividing forest cover change into forest gain and loss - Yuying Lin; Xueman Zuo; Aifang Weng; Mir Muhammad Nizamani; Yidong Jin; Linsheng Wen; Qing Zhao; Baoyin Li (Journal of Cleaner Production, 2024)

Optical investigation on effects of diesel injection strategy on ammonia/diesel dual fuel combustion characteristics and flame development - Wenpeng Zeng; Wanchen Sun; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Genetic variants in m5C modification genes are associated with survival of patients with HBV-related hepatocellular carcinoma - Bowen Chen; Moqin Qiu; Rongbin Gong; Yingchun Liu; Zihan Zhou; Qiuping Wen; Xiaoxia Wei; Xiumei Liang; Yanji Jiang; Peiqin Chen; Yuying Wei; Qiongguang Huang; et al. (Archives of Toxicology, 2024)

Mitochondrial Dysfunction due to Novel COQ8A Variation with Poor Response to CoQ10 Treatment: A Comprehensive Study and Review of Literatures - Jiayin Wang; Yan Lin; Zhihong Xu; Chuanzhu Yan; Yuying Zhao; Kunqian Ji (The Cerebellum, 2024)

Enhancing the component intra- and interrelationship of Elymus nutans mono- and mixed sowing communities via adjusting sowing patterns in the Qinghai Tibetan Plateau - Wen Ren; Changxing Lin; Jingyong Ma; Zhixin Zhang; Yuying Shen (Science of The Total Environment, 2024)

Unraveling how Fe-Mn modified biochar mitigates sulfamonomethoxine in soil water: The activated biodegradation and hydroxyl radicals formation - Yuying Wang; Haohao Lyu; Yuqian Du; Qilu Cheng; Yuxue Liu; Junwei Ma; Shengmao Yang; Hui Lin (Journal of Hazardous Materials, 2024)

Region and cloud regime dependence of parametric sensitivity in E3SM atmosphere model - Yun Qian; Zhun Guo; Vincent E. Larson; L. Ruby Leung; Wuyin Lin; Po-Lun Ma; Hui Wan; Hailong Wang; Heng Xiao; Shaocheng Xie; Ben Yang; Kai Zhang; et al. (Climate Dynamics, 2024)
The Department of Energy (DOE)’s Energy Exascale Earth System Model (E3SM), including its atmosphere model (EAM), has many relatively new features. In a previous study we conducted a systematic parametric sensitivity analysis for EAM based on short, perturbed parameter ensemble (PPE) simulations, mainly focusing on global mean climate features and metrics. While parameter values in global climate models are generally invariant in space and time, model response to parameters perturbation may vary by regions and climate regimes, which motivates the need to better understand the EAM model behaviors and physics at regional scale and process level. In this study, using the same set of PPE simulations and a similar sensitivity analysis framework, we identify parameters that cause largest sensitivities over different regions and compare model responses in fast atmospheric processes to the parameters across different cloud regimes for several important cloud-related fidelity metrics. We find that cloud forcing has opposite response to some parameters over mid-latitude vs. tropical land. We also analyze how the parametric sensitivity varies as stratocumulus transitions to shallow convection and to deep convection over ocean. Low cloud forcing and shortwave cloud forcing in the subtropical eastern Pacific are most sensitive to the parameters controlling the width of the probability density function (PDF) of the subgrid vertical velocity ( w’ ) ( gamma ) and the damping of the w’ skewness ( c8 ) near the coast but become more sensitive to the parameter affecting the damping of the w’ variance ( c1 ) further offshore. Detailed interpretation of the spatial dependence of parametric sensitivity is provided. We also investigate how the parametric sensitivity evolves with prediction duration. This study improves our process-level understanding of cloud physics and parameterization and provides insights for developing more advanced regime-aware parameterization schemes in global climate model.

Optical diagnostic study of internal and external EGR combined with oxygenated fuels of n-butanol, PODE3 and DMC to optimize the combustion process of FT synthetic diesel - Wanchen Sun; Genan Zhu; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Wenpeng Zeng; Xin Zhang; Mengqi Jiang; Changyou Yu (Fuel, 2024)

Degradation of bisphenol A by Fe-doped BiOBr enhanced UV/persulfate system: Significant role of superoxide radicals - Zezheng Lin; Yang Guo; Xiaoxuan Qu; Yuying Xiang; Shuwen Shen; Xin Zhu (Process Safety and Environmental Protection, 2023)

Oxidative abatement of saccharin by ozone and its influence on DBPs formation during postchlorination - Zezheng Lin; Yang Guo; Xiaoxuan Qu; Yuying Xiang; Xin Zhu (Journal of Water Process Engineering, 2023)

Impact of L-arginine on the quality of heat-treated Antarctic krill: Influence of pH and the guanidinium group - Xiang Ren; Xinyu Zhang; Peizi Sun; Junxin Lin; Yuying Zhang; Dongmei Li (Food Research International, 2023)

In vivo-in vitro correlations (IVIVC) for the assessment of pyrethroid bioavailability in honey - Yuying Liu; Siyuan Jiang; Yuxin Xiang; Fengxiang Lin; Xingyu Yue; Minkun Li; Jinjing Xiao; Haiqun Cao; Yanhong Shi (Food Chemistry, 2023)

Genome architecture and tetrasomic inheritance of autotetraploid potato - Zhigui Bao; Canhui Li; Guangcun Li; Pei Wang; Zhen Peng; Lin Cheng; Hongbo Li; Zhiyang Zhang; Yuying Li; Wu Huang; Mingwang Ye; Daofeng Dong; et al. (Molecular Plant, 2023)

Effects of conservation tillage on soil enzyme activities of global cultivated land: A meta-analysis - Linsheng Wen; Yun Peng; Yunrui Zhou; Guo Cai; Yuying Lin; Baoyin Li (Journal of Environmental Management, 2023)

An optical study of the combustion and flame development of ammonia-diesel dual-fuel engine based on flame chemiluminescence - Wanchen Sun; Wenpeng Zeng; Liang Guo; Hao Zhang; Yuying Yan; Shaodian Lin; Genan Zhu; Mengqi Jiang; Changyou Yu; Fei Wu (Fuel, 2023)

Adjusting spatial use to establish productive and stable Elymus nutans monocultures and mixed sowing systems - Wen Ren; Zhixin Zhang; Yuying Shen; Changing Lin; Xianlong Yang; Guohui Wang; Kun Yang; Mazuoma Mi; Ye Liu; Hui Wang (Field Crops Research, 2023)

Isolation and characterization of 32 SNP markers in Spinibarbus hollandi based on restriction site-associated DNA sequencing (RADseq) - Wenwei Huang; Jiangwei Zhou; Huawei Zhan; Yuying Zhang; Suhan Peng; Wenjun Li; Zusheng Yi; Lin Gui; Chong Han; Qiang Li (Conservation Genetics Resources, 2023)

Designing low-carbon cement-free binders for stabilization/solidification of MSWI fly ash - Chen Sun; Weizhe Ge; Yuying Zhang; Lei Wang; Yan Xia; Xiaoqing Lin; Qunxing Huang; Shengyong Lu; Daniel C.W. Tsang; Jianhua Yan (Journal of Environmental Management, 2023)

Carbon distribution and multi-criteria decision analysis of flexible waste biomass smouldering processing technologies - Yuying Chen; Shaorun Lin; Yunzhu Qin; Nicholas C. Surawski; Xinyan Huang (Waste Management, 2023)

Coupling activation and curing to tune the permselectivity of poly(piperazine amide) nanofiltration membranes - Dongsheng Zhao; Jiyu Song; Yiwen Zhang; Zhiquan Lin; Bo He; Nanfu Qiao; Kangping Huang; Wei Zhang; Shuang Ge; Yuying Li; B. Larry Li; Kang Xie; et al. (Journal of Water Process Engineering, 2023)

Plant and fungal species interactions differ between aboveground and belowground habitats in mountain forests of eastern China - Teng Yang; Leho Tedersoo; Pamela S. Soltis; Douglas E. Soltis; Miao Sun; Yuying Ma; Yingying Ni; Xu Liu; Xiao Fu; Yu Shi; Han-Yang Lin; Yun-Peng Zhao; et al. (Science China Life Sciences, 2023)

A novel coefficient of frosting suppression based on the real-time operating characteristics of air source heat pumps - Yao Lin; Yuying Sun; Jianfei Luo; Wenzhe Wei; Wei Wang; Qing Luo; Shengnan Liu; Shiming Deng (Energy and Buildings, 2023)

Advancing charge carriers separation and transformation by nitrogen self-doped hollow nanotubes g-C3N4 for enhancing photocatalytic degradation of organic pollutants - Xinlan Zhen; Changzheng Fan; Lin Tang; Jun Luo; Linrui Zhong; Yuying Gao; Mingjuan Zhang; Jangfu Zheng (Chemosphere, 2023)

Insecticide resistance and its underlying synergism in field populations of Spodoptera frugiperda (J. E. Smith) from Hainan Island, China - Junbin Liu; Zheng Hao; Shengyuan Yang; Yuying Lin; Hao Zhong; Tao Jin (Phytoparasitica, 2022)

Transcriptomic analyses provide insight into adventitious root formation of Euryodendron excelsum H. T. Chang during ex vitro rooting - Yuping Xiong; Shuangyan Chen; Zhenpeng Wei; Xiaohong Chen; Beiyi Guo; Ting Zhang; Yuying Yin; Xincheng Yu; Jinhui Pang; Meiyun Niu; Xinhua Zhang; Yuan Li; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Simulating the impacts of fishing on central and eastern tropical Pacific ecosystem using multispecies size-spectrum model - Qinqin Lin; Yuying Zhang; Jiangfeng Zhu (Acta Oceanologica Sinica, 2022)

Gene duplication to the Y chromosome in Trinidadian Guppies - Yuying Lin; Iulia Darolti; Benjamin L. S. Furman; Pedro Almeida; Benjamin A. Sandkam; Felix Breden; Alison E. Wright; Judith E. Mank (Molecular Ecology, 2022)
Differences in allele frequencies at autosomal genes between males and females in a population can result from two scenarios. First, unresolved sexual conflict over survival can produce allelic differentiation between the sexes. However, given the substantial mortality costs required to produce allelic differences between males and females at each generation, it remains unclear how many loci within the genome experience significant sexual conflict over survival. Alternatively, recent studies have shown that similarity between autosomal and Y sequences can create perceived allelic differences between the sexes. However, Y duplications are most likely in species with large nonrecombining regions, in part because they simply represent larger targets for duplications. We assessed the genomes of 120 wild‐caught guppies, which experience extensive predation‐ and pathogen‐induced mortality and have a relatively small ancestral Y chromosome. We identified seven autosomal genes that show allelic differences between male and female adults. Five of these genes show clear evidence of whole or partial gene duplication between the Y chromosome and the autosomes. The remaining two genes show evidence of partial homology to the Y. Overall, our findings suggest that the guppy genome experiences a very low level of unresolved sexual conflict over survival, and instead the Y chromosome, despite its small ancestral size and recent origin, may nonetheless accumulate genes with male‐specific functions.

Thermal treatment’s enhancement on high solid anaerobic digestion: effects of temperature and reaction time - Yuan Lin; Zuwen Liu; Yuying Hu; Fangyu He; Shi Yang (Environmental Science and Pollution Research, 2021)

Identification and Sexually Dimorphic Expression of a FoxL2-like Gene in Mud Crab (Scylla paramamosain): Potential Roles in Male Differentiation and Development - Yuying Yuan; Jiali Lin; Xueying Tan; Xi Shi; Shaobin Fang; Yin Zhang; Hongyu Ma; Fan Lin (Thalassas: An International Journal of Marine Sciences, 2021)

Amniotic fluid mesenchymal stem cells repair mouse corneal cold injury by promoting mRNA N4-acetylcytidine modification and ETV4/JUN/CCND2 signal axis activation - Xinfeng Fei; Yuying Cai; Feng Lin; Yongyi Huang; Te Liu; Yan Liu (Human Cell, 2021)
Severe corneal injury is one of the main causes of loss of visual function. Mesenchymal stem cells (MSCs) have the ability to repair damaged cells in vivo. The present study aimed to explore whether MSCs could function as a cell therapy tool to replace traditional methods to treat corneal injury. CD44 + /CD105 + mesenchymal stem cells isolated from mouse amniotic fluid (mAF-MSCs) were injected into mice after cryoinjury to induce corneal endothelial cell injury. Histopathological assays indicated that mAF-MSCs could promote the growth of corneal epithelial cells, reduce keratitis, and repair the corneal damage caused by low temperature. cDNA microarray analysis revealed that the mAF-MSCs affected the expression patterns of mRNAs related to cell proliferation and differentiation pathways in the mice after transplantation. The results of quantitative real-time PCR and western blotting revealed that NAT12, NAT10, and the ETV4/JUN/CCND2 signaling axis were elevated significantly in the mAF-MSC-transplantation group, compared with those in the phosphate-buffered saline-treated groups. High performance liquid chromatography–mass spectroscopy results revealed that mAF-MSCs could promote mRNA N4-acetylcytidine (ac4C) modification and high expression of N -acetyltransferase in the eyeballs. RNA immunoprecipitation-PCR results showed that a specific product comprising Vegfa , Klf4 , Ccnd2 , Jun , and Etv4 mRNA specific coding region sites could be amplified using PCR from complexes formed in mAF-MSC-transplanted samples cross-linked with anti-ac4C antibodies. Thus, mouse amniotic fluid MSCs could repair the mouse corneal cold injury by promoting the ETV4/JUN/CCND2 signal axis activation and improving its stability by stimulating N4-acetylcytidine modification of their mRNAs.

Molecular cloning, characterization and expression profiles of a SoxB2 gene related to gonadal development in mud crab ( Scylla paramamosain ) - Jiali Lin; Yuying Yuan; Xi Shi; Shaobin Fang; Yin Zhang; Mengyun Guan; Zhuofang Xie; Hongyu Ma; Fan Lin (Invertebrate Reproduction & Development, 2020)

Influence of coexisting calcium and magnesium ions on phosphate adsorption onto hydrous iron oxide - Jianwei Lin; Yuying Zhao; Yanhui Zhan; Yan Wang (Environmental Science and Pollution Research, 2020)

Assessment of iron-modified calcite/zeolite mixture as a capping material to control sedimentary phosphorus and nitrogen liberation - Yanhui Zhan; Yang Yu; Jianwei Lin; Xiaolong Wu; Yan Wang; Yuying Zhao (Environmental Science and Pollution Research, 2020)

Four LysR-type transcriptional regulator family proteins (LTTRs) involved in antibiotic resistance in Aeromonas hydrophila - Yuying Fu; Qilan Cai; Yuqian Wang; Wanxin Li; Jing Yu; Guidi Yang; Wenxiong Lin; Xiangmin Lin (World Journal of Microbiology and Biotechnology, 2019)

Understanding driving patterns of carbon emissions from the transport sector in China: evidence from an analysis of panel models - Danting Lin; Lanyi Zhang; Cheng Chen; Yuying Lin; Jiankai Wang; Rongzu Qiu; Xisheng Hu (Clean Technologies and Environmental Policy, 2019)

Assessment of sediment capping with zirconium-modified bentonite to intercept phosphorus release from sediments - Jianwei Lin; Siqi He; Yanhui Zhan; Zhe Zhang; Xiaolong Wu; Yang Yu; Yuying Zhao; Yan Wang (Environmental Science and Pollution Research, 2019)

A quantitative method for risk assessment of agriculture due to climate change - Zhiqiang Dong; Zhihua Pan; Pingli An; Jingting Zhang; Jun Zhang; Yuying Pan; Lei Huang; Hui Zhao; Guolin Han; Dong Wu; Jialin Wang; Dongliang Fan; et al. (Theoretical and Applied Climatology, 2018)

Transcriptional responses to drought stress in root and leaf of chickpea seedling - Xiansheng Wang; Ying Liu; Yuying Jia; Hanyan Gu; Hongyu Ma; Tian Yu; Hua Zhang; Quanjia Chen; Lin Ma; Aixing Gu; Jusong Zhang; Shubing Shi; et al. (Molecular Biology Reports, 2012)

Identification and characterization of a LEA family gene CarLEA4 from chickpea (Cicer arietinum L.) - Hanyan Gu; Yuying Jia; Xiansheng Wang; Quanjia Chen; Shubing Shi; Lin Ma; Jusong Zhang; Hua Zhang; Hao Ma (Molecular Biology Reports, 2012)

Molecular cloning and characterization of an F-box family gene CarF-box1 from chickpea (Cicer arietinum L.) - Yuying Jia; Hanyan Gu; Xiansheng Wang; Quanjia Chen; Shubing Shi; Jusong Zhang; Lin Ma; Hua Zhang; Hao Ma (Molecular Biology Reports, 2012)

Clinical Evaluation of Targeted Arterial Infusion of Verapamil in the Interventional Chemotherapy of Primary Hepatocellular Carcinoma - Jin Huang; Qiaohong Duan; Pingsheng Fan; Chushu Ji; Yuying Lv; Xinmin Lin; Liting Qian; Xiukun Yu (Cell Biochemistry and Biophysics, 2011)

A new 5,11-epoxymegastigmane glucoside from Acanthus ilicifolius - Changhong Huo; Hong Liang; Guangzhong Tu; Yuying Zhao; Wenhan Lin (Natural Product Research, 2008)

Analysis of heat-shock protein70 gene polymorphisms and the risk of Parkinson?s disease - Chiung-Mei Chen; Yuying Hsu; Sih-Jing Lin; Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Cheng-Kuang Wang; Yi-Ying Lin; Yih-Ru Wu; Hon-Chung Fung (Human Genetics, 2004)